2021
DOI: 10.1007/s11605-021-05021-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller-Dor Is an Effective Treatment for Esophageal-Gastric Junction Outflow Obstruction

Abstract: Background The treatment of esophagogastric junction outflow obstruction (EGJOO) currently mirrors that of achalasia, but this is based on only a few studies on small case series. The aim of this prospective, controlled study was to assess the outcome of laparoscopic Heller-Dor (LHD) in patients with EGJOO, as compared with patients with esophageal achalasia. Materials and Methods Between 2016 and 2019, patients with manometric diagnosis of idiopathic EGJO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Patients with a hypertensive LES or true gastroesophageal junction outflow obstruction (GEJOO) have a high intrabolus pressure and require a myotomy of the sphincter to relieve dysphagia. 25,26 The other observation is that even surgeons, who do not tailor fundoplication, obtain HRM prior to MSA. This suggests that even this group of surgeons believe that there is a level of outflow resistance at the GEJ that induces dysphagia in patients with inadequate peristaltic contraction.…”
Section: The Inconsistency In Literature Regarding Tailoring Approachmentioning
confidence: 99%
“…Patients with a hypertensive LES or true gastroesophageal junction outflow obstruction (GEJOO) have a high intrabolus pressure and require a myotomy of the sphincter to relieve dysphagia. 25,26 The other observation is that even surgeons, who do not tailor fundoplication, obtain HRM prior to MSA. This suggests that even this group of surgeons believe that there is a level of outflow resistance at the GEJ that induces dysphagia in patients with inadequate peristaltic contraction.…”
Section: The Inconsistency In Literature Regarding Tailoring Approachmentioning
confidence: 99%
“…During the drafting of the present study, patients were also contacted telephonically to obtain an update on their clinical conditions. Treatment failure was defined as the persistence or recurrence of an Eckardt score > 3, or the need for further treatment (pneumatic dilation, POEM, redo-myotomy or esophagectomy) [13]. Fig.…”
Section: Postoperative Assessmentmentioning
confidence: 99%
“…One group of investigators found that 55% of their EGJOO patients had an achalasia-like disorder as determined by a substantial drop in IRP during HRM with the administration of the smooth muscle relaxant amyl nitrite [45], and patients with achalasia-like EGJOO can respond well to typical achalasia treatments [46]. A recent prospective study of 25 such EGJOO patients showed that Heller myotomy was safe and effective in reducing symptoms as determined by the Eckardt score [47]. Thus, FLIP panometry can help guide treatment – if FLIP provides support for primary LES dysfunction as the etiology for EGJOO, then invasive treatment aimed at the LES (botulinum toxin injection, pneumatic dilation, Heller myotomy, peroral endoscopic myotomy (POEM)) might be warranted.…”
Section: Functional Luminal Imaging Probe Panometry Guiding Esophagog...mentioning
confidence: 99%